Preparation of Xylan–Acrylic Acid Polymer with High Molecular Weight and its Application as a Dye Removal Flocculant. (4th March 2019) - Xu, Dingding; Liu, Zhongming; Zhou, Wanpeng; Zhao, Xin; Fu, Chenglong; Fatehi, Pedram; Kong, Fangong; Yang, Guihua; Wang, Shoujuan
Abstract : Xylan is found in natural products and can be used for preparing value-added products. The main purpose of this study was to produce a xylan-based polymer (xylan–acrylic acid [Xy–AA]) as a flocculant for removing ethyl violet dye from wastewater. In this study, the polymerization reaction of xylan and acrylic acid (AA) was optimized by response surface methodology (RSM). It was indicated that the maximum charge density of –5.87 mmol/g and molecular weight of 352, 028 g/mol were obtained for Xy–AA polymer under the conditions of 20.53 g/L xylan concentration, 0.31 xylan/AA molar ratio, 2.5 h reaction time, and 72 °C reaction temperature. The polymer was characterized by charge density analyzer, Fourier transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance ( 1 H-NMR), and thermogravimetric analysis (TGA). The application of the product as a flocculant for removing the ethyl violet from simulated dye solution was evaluated. The results showed that the optimal dye removal of 97.08% was achieved under the conditions of 50 mg/L dye concentration, 120 mg/L Xy–AA concentration, pH 10, and 30 °C. The flocculation mechanism was also discussed.